WORKSHOP GOOGLE GEMINI UNTUK MENINGKATKAN PENGETAHUAN SISWA-SISWI DI SMP NEGERI 1 KANDANGSERANG - Prayogo Pujiono, Imam; Sopiah, Sopiah; Hikmah Sofyan, Nurul; Arifin, Jainul (Jurnal Pengabdian Masyarakat Polmanbabel, 2024)
The development of information technology has had a significant effect on various aspects of life, especially in education. Information technology is a technology applied to organise, store, and convert data into useful information through various methods. One of the technologies that helps obtain information is artificial intelligence (AI). AI is a technology that makes it possible to perform tasks that humans could only do in the past, such as human-machine communication, often called chatbots. One of the most advanced chatbots is Google Gemini. In education, Google Gemini can help students find answers to their questions and support independent learning. SMP Negeri 1 Kandangserang is a school in a mountainous area with poor road conditions. These road conditions cause many students to choose to study independently at home when the rainy season arrives. For this reason, community service was carried out by holding a Google Gemini workshop to help improve students' knowledge at SMP Negeri 1 Kandangserang when studying independently at home. 30 participants attended the workshop, and the presentation methods and hands-on practice were used at www.gemini.google.com. Pre-Test and Post-Test were conducted to measure participants' abilities before and after the workshop. The result of this activity is the increased ability of participants to use Google Gemini as a learning tool. This can be seen from the results of the Pre-Test and Post-Test questionnaires, which show an average increase of 21.67 participants or 72.22% of participants who previously stated that they could not use Google Gemini to do a command to be able to use it. Suggestions for participants are expected to continue exploring the capabilities of Google Gemini to help their learning process.